2021
DOI: 10.1186/s12964-021-00721-2
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock: a regulator of the immunity in cancer

Abstract: The circadian clock is an endogenous timekeeper system that controls and optimizes biological processes, which are consistent with a master circadian clock and peripheral clocks and are controlled by various genes. Notably, the disruption of circadian clock genes has been identified to affect a wide range of ailments, including cancers. The cancer-immunity cycle is composed of seven major steps, namely cancer cell antigen release and presentation, priming and activation of effector immunity cells, trafficking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 118 publications
1
45
0
1
Order By: Relevance
“…In our study cohort, we found a significant underexpression of PER1/2/3, CRY1/2 and NR1D1 proteins in CRC versus normal tissue, indicating an important role of these genes in colorectal carcinogenesis. This aspect has been extensively reported in a wide range of cancers, including CRC [22,[39][40][41]. Polymorphic variants of these circadian genes might contribute to an individual's risk of developing cancer [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 90%
“…In our study cohort, we found a significant underexpression of PER1/2/3, CRY1/2 and NR1D1 proteins in CRC versus normal tissue, indicating an important role of these genes in colorectal carcinogenesis. This aspect has been extensively reported in a wide range of cancers, including CRC [22,[39][40][41]. Polymorphic variants of these circadian genes might contribute to an individual's risk of developing cancer [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 90%
“…A series of gradual steps, called the Cancer-Immunity Cycle, are needed to iteratively inspire and expand in order for the anti-cancer immune response to effectively kill tumor cells [ 17 , 18 ]. The stimulus and inhibitory factors play a significant role in coordinately regulating every stage of the Cancer-Immunity Cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, there has been a paradigm shift on the role of the immune system in cancer therapy, with several new therapies that are now FDAapproved to enhance and even engineer the immune system to attack tumors. Some of these new therapies may benefit from chronotherapy because the tumor molecular clock influences the tumor microenvironment and immune cell infiltration (Cash et al, 2021;Z. Zhang et al, 2021b).…”
Section: Circadian Regulation Of the Tumor Cell Cycle Can Affectmentioning
confidence: 99%